METODE BERMAIN UNTUK MENINGKATKAN GERAK DASAR LARI SDN LOWOKWARU 5 KOTA MALANG - Yulyanto Sudjono Putra, Fajar; Usman Wahyudi; Bagus Eko Prasetyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the basic running movement skills of third-grade students of SDN Lowokwaru 5 through the application of play methods. Classroom Action Research was used in this study, with the implementation of 2 cycles consisting of planning phases, treatment implementation, observation, and reflection. Third-grade students consisting of 25 students became the research subjects. Documentation and field notes were used as data collection techniques. Data were analyzed using a quantitative approach. Data were collected through a 30-meter running speed test conducted in the yard of SDN Lowokwaru 5 as the instrument. The results showed that the use of play methods provided gradual improvements to students. The pre-cycle results showed an average score of 69.6 with 52% completeness. After the implementation of the action, the average increased to 72.8 in cycle I (64% complete) and 76.8 in cycle II (72% complete). Play methods in learning can provide a fun learning environment, encourage active involvement, and facilitate optimal mastery of running movements.